Prostatic disorders in acromegalic patients experience of a Brazilian center - Correa,Livia L. (2013)
Introduction Published data suggest that patients with acromegaly have an increased prevalence of prostate disorders. Objective To evaluate prostatic disorders in acromegalic patients comparing these results after one year of treatment of acromegaly and with a group of healthy men. Materials and Methods This study was composed of two parts: sectional study comparing patients with healthy controls (baseline) and prospective, longitudinal study (at baseline and after one year of treatment). Forty acromegalic patients were enrolled and evaluated at baseline and after one year with the application of international prostatic symptoms score (IPSS), digital rectal examination, measurements of growth hormone (GH), insulin-like growth factor-I (IGF-I), insulin-like growth factor-binding protein-3 (IGFBP-3), sex hormone-binding globulin (SHBG), prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), total testosterone, total and free prostate-specific antigen (PSA) levels and prostate ultrasonography (US). Thirty healthy men were selected as control group. Results We stratified patients and controls according to age, considering 40 years-old as cut off. Healthy controls under 40 had IPSS values lower than acromegalic patients. When considering only older patients and controls prostate hyperplasia and structural abnormalities were more frequent in acromegalics. After one year of treatment there was significant decrease in GH, IGF-I and prostate volume in acromegalics over 40 years-old. Conclusions Acromegalics under 40 have more urinary symptoms according to IPSS and above 40 years-old higher frequency of structural changes and increased prostate volume than healthy men. Significant reduction of GH and IGF-I levels during treatment of acromegaly leads to decrease in the prostate volume.